Corticosteroid Use in the Treatment of COVID-19: A Multicenter Retrospective Study in Hunan, China - Ma, Yiming; Zeng, Huihui; Zhan, Zijie; Lu, Huanhuan; Zeng, Zihang; He, Chenjie; Liu, Xiangming; Chen, Chen; Qin, Qingwu; He, Jia; Zhou, Zhiguo; Huang, Peng; et al. (Frontiers in Pharmacology, 2020)
Background: Coronavirus disease 2019 (COVID-19) has developed into a worldwide pandemic. This study aimed to retrospectively describe the use of corticosteroids in treating COVID-19. Methods: For this multicenter retrospective study, medical records from 488 symptomatic COVID-19 patients were reviewed. Patients were divided into severe and non-severe groups. Baseline characteristics, signs and symptoms, laboratory findings, treatments and disease outcomes were compared. Specific data for corticosteroid treatment were further analyzed. Results: 450 COVID-19 patients were included in this study, including 82 severe patients and 368 non-severe cases. Out of the 450 patients, 126 (28.0%) received corticosteroid treatment. In the 126 patients treated with corticosteroids, the median daily dose of corticosteroid therapy was 56.6 (interquartile range [IQR]: 40.0–78.4) mg and median corticosteroid therapy duration was 5.0 (IQR: 3.0–7.0) days. Among non-severe cases, patients treated with corticosteroids were significantly older in comparison with patients who did not receive corticosteroid treatment (p<0.01); the proportion of patients receiving antibiotic therapy in the corticosteroid group was significantly higher than that in the non-corticosteroid group (p<0.001); hospitalization length and duration of viral shedding were significantly longer in patients in the corticosteroid group than in the non-corticosteroid group after adjusting for age, sex, and comorbidities (p<0.05). In severe cases, patients treated with corticosteroids were significantly older and comorbidities at admission were significantly more common in patients receiving corticosteroid treatment (p<0.05); the proportion of patients receiving antibiotic therapy in the corticosteroid group was significantly higher than that in the non-corticosteroid group (p<0.001); no significant difference in hospitalization length or viral shedding duration was found between two groups after adjusting for age, sex, and comorbidities (p>0.05). Conclusion: Our study indicates that corticosteroids are regarded as one of treatments in the general clinical practice of COVID-19. However, corticosteroid use may be accompanied by increased use of antibiotics, longer hospitalization, and prolonged viral shedding.